2005
DOI: 10.1007/s10658-004-8233-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide localization and antioxidant status in the recovery of apricot plants from European Stone Fruit Yellows

Abstract: Hydrogen peroxide (H2O2) localization and roles of peroxidases, malondialdehyde and reduced glutathione\ud were compared in leaves of apricot (Prunus armeniaca) plants: asymptomatic, European Stone Fruits\ud Yellows (ESFY)-symptomatic and recovered. Nested PCR analysis revealed that ‘Candidatus Phytoplasma\ud prunorum’, is present in asymptomatic, symptomatic and recovered apricot trees, confirming previous\ud observations on this species, in which recovery does not seem to be related to the disappearance of\u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“…1). H 2 O 2 overproduction occurred in phytoplasma-infected apple and apricot trees (Musetti et al 2004(Musetti et al , 2005. In the present study, the absence of H 2 O 2 overproduction in phytoplasma-free plants likely occurred because they lacked pathogen-induced oxidative stress.…”
Section: H 2 O 2 Contentmentioning
confidence: 51%
“…1). H 2 O 2 overproduction occurred in phytoplasma-infected apple and apricot trees (Musetti et al 2004(Musetti et al , 2005. In the present study, the absence of H 2 O 2 overproduction in phytoplasma-free plants likely occurred because they lacked pathogen-induced oxidative stress.…”
Section: H 2 O 2 Contentmentioning
confidence: 51%
“…Because of the wide array of symptoms expressed by diseased plants, nutrient depletion is probably not restricted to sugars, but also includes other compounds. A reduction in the concentration of photosynthetic pigments [137] and of total soluble proteins [137]- [139], as well as alterations in the hormone balance [135] [140], amino-acid transport [134] and the occurrence of folate and endopetidase gene homologues in phytoplasma genomes [141] were described as potentially affecting host plants infected with different phytoplasmas.…”
Section: Virulence and Pathogenicitymentioning
confidence: 99%
“…Lots of reports demonstrated that wounding and applied JA could induce oxidative stress [23], which was also observed in the wounded pea seedlings (Fig. 5).…”
Section: Lox/aos Played Important Roles In Defense Response Of Pea Sementioning
confidence: 75%